Enhancing EFL Reading: Student Teachers' Metacognitive Practices in Islamic Higher Education - Erlina, Dian; Marzulina, Lenny; Holandyah, Muhammad; Herizal; Fajrin, Nyayu (Edukasi, 2025)
Metacognition refers to the awareness and regulation of one’s cognitive processes. In the context of reading, it involves the employment of metacognitive strategies to promote reading comprehension. This qualitative case study aims to explore the perceptions of English as a Foreign Language (EFL) student teachers regarding their reading processes and the strategies they consider effective. The research focuses on the metacognitive reading experiences of EFL student teachers who were purposively selected from an Islamic university in Palembang, South Sumatra, Indonesia. To gather data, semi-structured interviews were conducted, allowing participants to reflect on their metacognitive reading practices. The thematic analysis of the interview data revealed that student teachers regarded metacognitive strategies as essential tools for enhancing reading comprehension. They employed a variety of metacognitive strategies to plan, monitor, and evaluate their reading processes. These strategies can be categorized into three distinct types: (1) global reading strategies, (2) problem-solving reading strategies, and (3) support reading strategies. Such strategies enable student teachers to reflect on their reading processes, navigate texts effectively, assess their understanding, identify difficulties, and adjust their approaches as necessary. This study emphasizes the importance of metacognitive strategies in reading and highlights the necessity of integrating strategic and reflective reading practices for EFL student teachers. This integration not only fosters their development as proficient readers but also equips them to teach these strategies effectively to their future students.